2005
DOI: 10.1254/jphs.fp0040793
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Herbal Medicine, Shengmai San, Is Effective for Improving Circulatory Shock and Oxidative Damage in the Brain During Heatstroke

Abstract: Abstract. The aim of this study was to investigate the effect of Shengmai San (SMS), a traditional Chinese herbal medicine, on heatstroke-induced circulatory shock and oxidative damage in the brain in rats. Anesthetized rats were exposed to a high ambient temperature (43°C) to induce heatstroke. After the onset of heatstroke, the values of mean arterial pressure, cerebral perfusion pressure, cerebral blood flow, and brain partial pressure of O 2 were all significantly lower than those in normothermic controls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…In addition, SMS effectively suppressed the ischemia-reperfusion injury during middle cerebral artery ligation (10) as well as the cerebral ischemia and damage during heat stroke (11) by reducing brain oxidative stress. However, it is not known whether prior administration of SMS is able to attenuate inflammatory cytokines and NO formation that occurred during heat stroke.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, SMS effectively suppressed the ischemia-reperfusion injury during middle cerebral artery ligation (10) as well as the cerebral ischemia and damage during heat stroke (11) by reducing brain oxidative stress. However, it is not known whether prior administration of SMS is able to attenuate inflammatory cytokines and NO formation that occurred during heat stroke.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that α-tocopherol treatment improved neurite outgrowth of cultured retinal ganglion cells (35). Having noted that the protective effects of SMS on oxidative damages in different kind of cells or tissues might be shared mechanistically with those of α-tocopherol, several studies reported similar protection by α-tocopherol (14,16,36,37). Our data showed that neurite outgrowth of DRG sensory neurons was enhanced to a similar level by treatment of either SMS or α-tocopherol in comparison to the untreated control, which implicates physiological significance of the antioxidant activity of SMS for axonal regeneration.…”
Section: Discussionmentioning
confidence: 97%
“…In this sense, traditional medicine formula used for disease prevention is an interesting target of study because their basic function is to modulate the physiological resistance against exogenous stimuli including oxidative stress through manipulating cellular processes (15). Recent reports demonstrated that Shengmai-san (SMS), a traditional Chinese medicine formula, significantly prevented the oxidative damage in heart, brain, and other tissues (4,16). We also showed that SMS had high antioxidant potential to prevent cerebral oxidative damages induced by ischemia-reperfusion treatment in experimental animals (17).…”
Section: Introductionmentioning
confidence: 99%